2018
DOI: 10.3390/molecules23092298
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Berberine on the Gut Microbiota in Apc min/+ Mice Fed with a High Fat Diet

Abstract: Background: Berberine (BBR) has been extensively reported to inhibit colorectal cancer (CRC) development, though its bioavailability is poor. Nowadays, an increasing number of studies have shown that BBR significantly accumulates in the intestines and could regulate gut microbiota in obesity. The purpose of this study was to further explore the effects of BBR on gut microbiota in Apc min/+ mice receiving a high fat diet (HFD). Methods: Apc min/+ mice received either HFD alone or HFD and BBR for 12 weeks. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…In line, recent CAC studies in mice demonstrate that enriching high-fat diets with TNF- and IL-6-inhibiting supplements leads to the reduction of inflammation and mucosal injury in the colons of mice and ultimately to less tumor development [189,190,191,192,193]. Similar effects on tumor burden are seen by reducing obesity-induced inflammation via natural substances in the diets of obese APC Min/+ mice [194,195].…”
Section: Obesity-induced Inflammation and Crcmentioning
confidence: 81%
“…In line, recent CAC studies in mice demonstrate that enriching high-fat diets with TNF- and IL-6-inhibiting supplements leads to the reduction of inflammation and mucosal injury in the colons of mice and ultimately to less tumor development [189,190,191,192,193]. Similar effects on tumor burden are seen by reducing obesity-induced inflammation via natural substances in the diets of obese APC Min/+ mice [194,195].…”
Section: Obesity-induced Inflammation and Crcmentioning
confidence: 81%
“…In addition, more recent attention has been turned to the correlation of gut microbiota and fecal metabolites in the progress of diseases, current literatures have also confirmed that metabolites played an important role in the pathological progression of CRC (35,36). Although the study had reported that BBR restored the gut microbiota and alleviated the development of CRC in Apc min/+ mice fed with HFD, the overall effect of BBR on both microorganisms and metabolites of CRC remains unknown (27). In this study, we adapted the commonly CRC model induced by AOM and DSS, and treated with or without BBR to illustrate the inhibitory effect of BBR on CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the therapeutic strategies for CRC have now shifted to the microbiome-metabolomics. Interestingly, BBR has been reported to regulate the gut microbiota diversity and community composition, which contributed to attenuate obesity and insulin resistance, as well as CRC in high-fat diet-fed rats ( 25 27 ), suggesting that BBR can treat diseases by modulating gut microbiota. Here, we hypothesized that the gut microbiota and its metabolites are the targets of BBR on the treatment of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with some previous findings obtained using ethanolic [50] and methanolic [51] B. vulgaris extracts, the extracts used in this study demonstrated excellent inhibition of α-glucosidase and α-amylase. An increasing number of studies have shown that berberine significantly accumulates in the intestines [52]. Therefore α-glucosidase and α-amylase inhibitory activity of glycerol and other B. vulgaris extracts can certainly contribute to well-established antidiabetic properties of berberine and plants that contain it.…”
Section: Discussionmentioning
confidence: 99%